Implementation of Humanistic Theory in Islamic Education Learning through Active Learning at SMP Negeri 52 Palembang - Chan, Rahul; Ali, Marwan; Harto, Kasinyo; Suryana, Ermis (UMSU, 2025)
This study aims to analyze the application of humanistic theory in learning Islamic Religious Education (PAI) through the Active Learning method at SMP Negeri 52 Palembang. Humanistic theory emphasizes the optimal development of individual potential by considering emotional, social, and affective aspects in the learning process. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation studies. The results showed that the integration of humanistic theory into the Active Learning method was able to increase students' motivation, independence, and active participation in PAI learning. Students become more involved in understanding religious concepts, develop critical thinking, and show more positive responses to learning materials. In addition, the data shows a significant increase in students' learning outcomes, with the completion rate reaching 87.50%. The findings show that the humanistic theory-based learning approach is effective in creating a conducive learning environment and empowering learners as a whole, especially in strengthening religious values. The implication of this research contributes to the development of PAI curriculum and learning strategies that are more humanistic and participatory.